Does trading anonymously enhance liquidity? - Patrick J. Dennis; Patrik Sandås (Sveriges Riksbank, 2014)
Anonymous trading is the norm in today's financial markets but there are a few exceptions. We study one such case, the OMX Nordic Exchanges (Stockholm, Helsinki, Copenhagen, and Reykjavik) that have traditionally been more transparent than most other markets. On June 2, 2008 OMX Nordic switched to making post-trade reporting anonymous for some of their markets. We exploit this quasi natural experiment to investigate the impact this change had on liquidity and trading behavior. Our difference-in-difference method reveals a modest, though statistically insignificant, 14 basis point improvement in the quoted spread under the post-trade anonymous regime. The price impact of a trade decreased by a statistically significant four basis points for seller-initiated trades and did not change for buyer-initiated trades.
Keywords: G10; G15; G14; 330; Anonymity; Transparency; Liquidity; Broker ID